Estudo clínico genético sobre a displasia coxofemoral em cães e sua associação ao polimorfismos de nucleotídeos simples (SNPs) candidatos - Conceição, Thais Figueiredo (2024)
Hip dysplasia (CD), characterized by abnormal laxity of the hip joint, predominantly affects medium and large dogs. This study aimed to investigate the incidence of CD through genetic analysis, using three single nucleotide polymorphisms (SNPs) associated with the disease in other breeds. This genetic approach seeks to enhance understanding of the genetic basis underlying CHD, with significant implications for early diagnosis and the development of more effective management and treatment strategies. Whole blood samples were collected from 61 individuals, processed for DNA extraction, polymerase chain reaction (PCR) amplification, and sequencing of the BICF2G630227898, BICF2G630339806, and BICF2S2459425 SNP regions. The results revealed that 96% of individuals had the BICF2G630227898 SNP, while 62% and 34% had the BICF2G630339806 and BICF2S2459425 SNPs, respectively. These findings contribute to a deeper understanding of the genetic predisposition to hip dysplasia, emphasizing the need for additional research to identify polymorphisms associated with the condition and to develop accurate diagnoses based on genetic analysis.